3D requirements visualization - Teyseyre, Alfredo Raúl (2003)
The importance of correctly determining the requirements of a system at the very beginning of the development process it is a well known fact. Experience shows that the incorrect definition of the requirements leads to the development of deficient systems, increases the cost of its development or even causes projects to fail. Therefore it is crucial for the clients to verify that the planned system satisfies their needs. This means that the system must be described in a form that clients can clearly understand it. In this context, visualization techniques appear as a useful tool to help the users in the process of requirements understanding and validation. This work proposes the use of 3D visualization techniques to validate the requirements of a system with the user. The use of these techniques can reduce the communication gap between the clients and the developers resulting in a much more effective process of requirements validation. The approach tries to take advantage of the benefits of the 3D visualization, complementing this with the advantages of formal specifications. A tool, called ReqViz3D, that materializes the proposal was developed. This tool allows to specify the requirements in the formal language Z, define a graphical representation of them, and create a 3D animated visualization of theirs execution through which the users can validate them.